Quantitative Susceptibility Mapping of Venous Vessels in Neonates with Perinatal Asphyxia - Weber, A.M.; Zhang, Y.; Kames, C.; Rauscher, A. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: Cerebral venous oxygen saturation can be used as an indirect measure of brain health, yet it often requires either an invasive procedure or a noninvasive technique with poor sensitivity. We aimed to test whether cerebral venous oxygen saturation could be measured using quantitative susceptibility mapping, an MR imaging technique, in 3 distinct groups: healthy term neonates, injured term neonates, and preterm neonates.MATERIALS AND METHODS: We acquired multiecho gradient-echo MR imaging data in 16 neonates with perinatal asphyxia and moderate or severe hypoxic-ischemic encephalopathy (8 term age: average, 40.0 [SD, 0.8]  weeks’ gestational age; 8 preterm, 33.5 [SD, 2.0]  weeks’ gestational age) and in 8 healthy term-age controls (39.3 [SD, 0.6] weeks, for a total of n = 24. Data were postprocessed as quantitative susceptibility mapping images, and magnetic susceptibility was measured in cerebral veins by thesholding out 99.95% of lower magnetic susceptibility values.RESULTS: The mean magnetic susceptibility value of the cerebral veins was found to be 0.36 (SD, 0.04) ppm in healthy term neonates, 0.36 (SD, 0.06) ppm in term injured neonates, and 0.29 (SD, 0.04) ppm in preterm injured neonates. Correspondingly, the derived cerebral venous oxygen saturation values were 73.6% (SD, 2.8%), 71.5% (SD, 7.4%), and 72.2% (SD, 5.9%). There was no statistically significant difference in cerebral venous oxygen saturation among the 3 groups (P = .751).CONCLUSIONS: Quantitative susceptibility mapping–derived oxygen saturation values in preterm and term neonates agreed well with values in past literature. Cerebral venous oxygen saturation in preterm and term neonates with hypoxic-ischemic encephalopathy, however, was not found to be significantly different between neonates or healthy controls.χmagnetic susceptibilityCSaO2cerebral arterial oxygen saturationCSvO2cerebral venous oxygen saturationHcthematocritHIEhypoxic-ischemic encephalopathyNIRSnear-infrared resonance spectroscopyQSMquantitative susceptibility mappingSSSsuperior sagittal sinusTRUSTT2-relaxation-under-spin tagging